Large cross-section rib silicon-on-insulator (SOI) S-bend waveguide - Nurdiani, Zamhari; Abang Annuar, Ehsan (Elsevier GmbH, 2017)
S-bend SOI waveguide is known as the most critical part for SOI device design. Normalized output power for the different parameter of the S-bend waveguide has been analyzed using OptiBPM simulator in 1.55 μm communication wavelength. Dimension of 5 × 5 μm2 single-mode rib waveguide is chosen. The variable parameters are transition offset and lateral offset, given the waveguide length of 100 μm–5000 μm. The maximum normalized output power achieved at the waveguide length of 550 μm for the 10 μm S-bend offset is 95.81%. Moreover, the ideal lateral offset is 2.7 μm with 2.52% normalized output power improvement.